Digital Health Value Realization Through Active Change Efforts - Bhyat, Rashaad; Hagens, Simon; Bryski, Katie; Kohlmaier, Jocelyn Fausto (Frontiers in Public Health, 2021)
Digital health has massive potential in health care but has been slow to evolve in comparison to other information-intensive industries. One of the key barriers has been the complex relationship between the perceived return on investment for the investor and the resulting value to patients and caregivers. Those actors who pay for technologies do not always see an appreciable return for themselves, while those actors who must apply the technology to generate value are not always incentivized to do so. This misalignment must be better understood and addressed to accelerate digital health. This paper will examine this challenge through the clinician experience, using empirical case examples from Canada to illustrate opportunities for change. While many factors may influence digital health adoption, this paper specifically aims to explore shifts in the balance of the perceived value of implementing digital health tools, versus the efforts required to adopt them. It will explore two contrasting case examples: clinical adoption of EMRs in Canada from 2009 to 2015, and clinical adoption of virtual care technologies during the COVID-19 pandemic from 2020 to 2021. In 2006, Canada lagged peer countries in the adoption of electronic medical records (EMR) in community-based care. Financial support and cooperation of multiple stakeholders were required to address the misaligned incentives. The rapid adoption of virtual care in Canada in response to the pandemic provides another example of the importance of alignment among the factors of clinical workflows, clinical appropriateness, technology integration and payment models. In both cases, the costs and effort of adopting new technologies outweighed direct clinician value, requiring change initiatives to catalyze progress. This imbalance could be unique to these examples in Canada and may not be globally generalizable to the adoption of all digital health tools. However, how change efforts can be tailored to adjust to a rapidly evolving health care workforce, spanning diverse jurisdictions and stakeholder groups will be critical to the sustainability of virtual care adoption. Using insights from successful change initiatives past and present, this paper aims to answer these questions to enable a smoother transition to digital health innovations of the future